DOD and DOA estimation in bistatic MIMO radar for nested and coprime array with closed-form DOF. Issue 5 (4th May 2017) - Zheng, Guimei; Tang, Jun
ABSTRACT: It is well known that sparse array can offer better angle resolution than that of uniform linear array (ULA) in the same number of physical sensors. But in bistatic minimum redundancy sparse array multi-input multi-output (MIMO) radar, it cannot offer closed-form degree of freedom (DOF) for the arbitrary number of sensors with direction of departure and direction of arrival estimation. Therefore, this article introduces a nested array and coprime array into sparse array to solve the problem. First, construct no holes difference-coarray by extracting specified covariance matrix elements. Then, transform the difference-coarray into ULA within bistatic MIMO radar through some mathematical operations. As a result, many angle estimation methods for traditional ULA can be applied to the sparse bistatic MIMO array radar. The proposed algorithm offers closed-form DOFs for sparse array and the array aperture is much larger than that of ULA with identical number of sensors. The usefulness of the proposed methods is verified through computer simulations.